Tree species composition of 0.1 ha plot at UiTM Jengka education forest (line 14) - Zulrofli, Siti Shariha; Mohd Redzwan, Zulaikha; Abdul Karim, Khairulanwar; Kahar, Sadam (2012)
The study was carried out to determine the species composition and density of the trees in 0.1 ha plot of forest education in UiTM Jengka on Plot 14. One plot of 20m X 50m (0.1 ha) was established in Line 14. A total of 177 individual tree with diameter at breast high (DBH) above 5 cm and above were defined in this study area which are comprises 177 tree are belongs to 33 families, 70 genera and 104 species. Compared to Turner (1995), the number of species, genera and families that are presence in this study plot was only represent 1.25 % species, 4.18% genera and 13.30 % families from the Peninsular Malaysia plants. In UiTM Jengka Education Forest, family from Euphorbiaceae is families that have a largest number of genera species and individual with 10 genera, 15 species and 42 individual. Artocarpus is genera with the highest number of species with 5 species which is 4.81 % from the total species in the study area. Croton was genus with the highest number of individual with 20 individual or 11.30 %.The Croton argyratus is the species that recorded highest number of individual with 20 individual or 11.30 %. There are 8 endemic species in Peninsular Malaysia recorded in this study plot which are dominated by Artocarpus hispidus with 3 individual endemic species. The density of 5 cm tree diameter at breast high (OSH) and above in the study are 177 individual / 0.1 ha or 1770 individual / ha. The community structures resulted that the DBH class with the 5 cm to 14.9 cm or 76.27 % juvenile trees dominates the distribution of individual of tree in this study.